An Academic Writing “Essay Writing Training Program for Senior High School Students at MAN Pematangsiantar” - Ika Purnama Sari; Epi Supriyani Siregar; Iin Parlina; Anita Purba; Arwin Tannuary; Asmarani Nasution; Rizky Khairunnisa Sormin (Salus Publica: Journal of Community Service, 2026)
This community service activity aimed to improve students’ essay writing skills through essay writing training conducted for senior high school students at MAN Pematangsiantar. Writing essays is an important academic skill that supports students’ literacy development, critical thinking, and academic writing ability. However, many students still faced difficulties in organizing ideas, developing paragraphs, and understanding essay structure. Therefore, essay writing training was conducted using lecture, discussion, practice, mentoring, and feedback methods. The activity was carried out through three stages: preparation, implementation, and evaluation. During the implementation stage, students learned essay structure, paragraph development, and transition signals, and then practiced writing essays based on selected topics. The results of this activity showed that students’ understanding of essay structure improved, students were able to organize ideas more systematically, and students’ motivation and confidence in writing also increased. The training also supported the school literacy program by encouraging students to express ideas in written form. In conclusion, essay writing training is effective in improving students’ writing skills and literacy competence. Therefore, similar training activities are recommended to be conducted continuously to support students’ academic writing skills.